REPRESENTASI PERDAMAIAN PADA IKLAN COCA-COLA EDISI : COCA-COLA SMALL WORD MACHINES-BRINGING INDIA AND PAKISTAN TOGETHER DI MEDIA YOUTUBE - Yessi Putri (Universitas Mercu Buana, 2017)
This study aims to find out the symbols used to present peace in the advertisements of “Coca-Cola Small Word Machines-Bringing India and Pakistan Together” published in the YouTube on May 19, 2013. In this study, we used qualitative methods with semiotics analysis of Roland Barthes. The peace symbols shown in Coca-Cola ads are meant to improve the relationships of conflict-ridden Indians and Pakistan over the years. In this regard, Coca-Cola companies are trying to find business opportunities as well as campaigning for peace through innovations in commercial advertising. The research concludes that there is a hidden agenda of advertising, not just aiming to unite Indians and Pakistanis but to take business advantage for the company from the conflict between India and Pakistan. The conclusion of this research is that the representation of peace done by Coca-Cola companies against the conflicts of India and Pakistan is a form of corporation in the form of an advertisement.Keywords: Marketing Communication, Advertising, Representation, Symbols, Peace